Perencanaan Peserta Didik di Mts Al Ghiffari Leuwiliang - Mutia Irmayanti; Endin Mujahiddin; Nesia Andriana; Ahmad; Rahmat Rosyadi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Student planning requires skill, foresight, sensitivity, seriousness and strong determination, and serious management to achieve the expected goals. The multiple intelligences possessed by students must be explored and developed through self-development programs according to their respective talents and interests. Therefore the school principal as a policy maker should produce policies so that the implementation of the learning process can run effectively. Discipline development must be planned as well as possible, both academic and non-academic development. This study used field research methods (Field Research) using a qualitative descriptive method. The observation was used as the data collection. Records and other documents were used to support the conducted research. The objects in this study were books, journals, and articles. The subjects in this study were the school principal and vice principal for student affairs. The results of this study indicated that student planning is the initial stage in doing something that begins with the analysis of students’ needs, Students’ Selection, Students’ Orientation, Students’ Placement, Students’ Records, and Reports. Student planning at MTs Al Ghiffari had been going well in terms of PPDB and students’ Orientation Period, but it needed to be maximized in terms of grouping students, fostering student discipline, and organizing special services